Análise do fragmento amino-terminal do pro-peptídeo natriurético tipo B e de fatores de risco para oclusão coronariana aterosclerótica angiográfica em pacientes com a hipótese diagnóstica de cardiopatia isquêmica - Ribeiro, Demóstenes Gonçalves Lima (2009)
Cardiovascular diseases, including ischemic heart disease, are the main causes of death in Brazil. Atherosclerosis is a chronic inflammatory disease that starts in the childhood, progresses slowly and shows up many decades later. It begins as an endothelial dysfunction and has as its main risk factors the male sex, age, smoking, hypercholesterolemia, arterial hypertension, diabetes mellitus and a background of early family atherosclerotic disease. The rise of many biochemical markers in the plasma signals the presence of inflammation in the atherosclerosis. The brain natriuretic peptide and the amino-terminal pro-B-type natriuretic peptide (NT-proBNP) also increase in coronary atherosclerosis. This is a cross-sectional and observational study of 153 in-patients at the Cardiology Ward of HUWC-UFC from 08.01.2007 to 03.31.2008 with the diagnostic hypothesis of Ischemic Heart Disease, i.e., stable angina, unstable angina or acute myocardial infarction. All of them underwent heart catheterization and coronary angiography. They were classified respectively as group A or B in accordance with the presence or not of angiographic atherosclerotic coronary occlusion. Patients were not included in the analysis if they had been submitted to surgical or percutaneous revascularization; had an acute or chronic dialytic kidney disease; cancer or infection; a lung, hepatic or hematopoietic disease; an acute or chronic inflammatory illness or associated myocardial, valvular or congenital heart disease. The two groups were analyzed in a similar way with regard to gender, age, level of education, body mass index, abdominal circumference, smoking, diabetes mellitus, arterial hypertension, an early atherosclerosis family history, the use of statin, presence of metabolic syndrome and clinical presentation of stable angina, unstable angina or acute myocardial infarction. The HDL-cholesterol, non HDL-cholesterol, a total cholesterol/HDL-cholesterol ratio < 5, a LDL-cholesterol/HDL-cholesterol ratio < 3.5, the creatinine and fibrinogen plasma concentration, the total leukocyte and monocyte count, the high-sensitivity C reactive protein, the NT-proBNP, the electrocardiogram, the chest radiography and the echocardiogram, with regard to the presence or not of systolic dysfunction, were also analyzed. The univariety analysis comparing both groups revealed that group A’ patients more frequently were diabetics and had systolic dysfunction, NT-proBNP ≥ 250 pg/ml, fibrinogen higher than 500 mg/dl, more frequent use of statin and 501 or more monocytes/mm3 than patients´ group B. Curiously, the body mass index ≥ 30 and abnormal abdominal circumference were more frequently found among patients with angiographic normal coronary arteries. Nevertheless, by multivariety regression logistic analysis the independent factors for angiographic atherosclerotic coronary occlusion were the NT-proBNP ≥ 250 pg/ml, diabetes mellitus, an increase of monocyte number and of fibrinogen plasma concentration, in spite of creatinine level and presence of systolic dysfunction. The model takes into account these factors has 80.4% sensitivity, 76.9% specificity and 79.7% of accuracy for the diagnostic of angiographic atherosclerotic coronary occlusion.